Delivering High-Quality Cancer Care: Charting a New Course for a System in Crisis - Institute of Medicine (The National Academies Press, 2013)
In the United States, approximately 14 million people have had cancer and more than 1.6 million new cases are diagnosed each year. However, more than a decade after the Institute of Medicine (IOM) first studied the quality of cancer care, the barriers to achieving excellent care for all cancer patients remain daunting. Care often is not patient-centered, many patients do not receive palliative care to manage their symptoms and side effects from treatment, and decisions about care often are not based on the latest scientific evidence. The cost of cancer care also is rising faster than many sectors of medicine—having increased to $125 billion in 2010 from $72 billion in 2004—and is projected to reach $173 billion by 2020. Rising costs are making cancer care less affordable for patients and their families and are creating disparities in patients' access to high-quality cancer care. There also are growing shortages of health professionals skilled in providing cancer care, and the number of adults age 65 and older—the group most susceptible to cancer—is expected to double by 2030, contributing to a 45 percent increase in the number of people developing cancer. The current care delivery system is poorly prepared to address the care needs of this population, which are complex due to altered physiology, functional and cognitive impairment, multiple coexisting diseases, increased side effects from treatment, and greater need for social support. Delivering High-Quality Cancer Care: Charting a New Course for a System in Crisis presents a conceptual framework for improving the quality of cancer care. This study proposes improvements to six interconnected components of care: (1) engaged patients; (2) an adequately staffed, trained, and coordinated workforce; (3) evidence-based care; (4) learning health care information technology (IT); (5) translation of evidence into clinical practice, quality measurement and performance improvement; and (6) accessible and affordable care. This report recommends changes across the board in these areas to improve the quality of care. Delivering High-Quality Cancer Care: Charting a New Course for a System in Crisis provides information for cancer care teams, patients and their families, researchers, quality metrics developers, and payers, as well as HHS, other federal agencies, and industry to reevaluate their current roles and responsibilities in cancer care and work together to develop a higher quality care delivery system. By working toward this shared goal, the cancer care community can improve the quality of life and outcomes for people facing a cancer diagnosis.
Keywords: Health and Medicine

Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer is the summary of a workshop convened by the Institute of Medicine's National Cancer Policy Forum in July 2013 to facilitate discussion about gaps and challenges in caring for adolescent and young adult cancer patients and potential strategies and actions to improve the quality of their care. The workshop featured invited presentations from clinicians and other advocates working to improve the care and outcomes for the adolescent and young adult population with cancer. Cancer is the leading disease-related cause of death in adolescents and young adults. Each year nearly 70,000 people between the ages of 15 and 39 are diagnosed with cancer, approximately 8 times more than children under age 15. This population faces a variety of unique short- and long-term health and psychosocial issues, such as difficulty reentering school, the workforce, or the dating scene; problems with infertility; cardiac, pulmonary, or other treatment repercussions; and secondary malignancies. Survivors are also at increased risk for psychiatric conditions such as anxiety, depression, substance abuse, and suicide and may have difficulty acquiring health insurance and paying for needed care. Identifying and Addressing the Needs of Adolescents and Young Adults with Cancer discusses a variety of topics important to adolescent and young adult patients with cancer, including the ways in which cancers affecting this group differ from cancers in other age groups and what that implies about the best treatments for these cancer patients. This report identifies gaps and challenges in providing optimal care to adolescent and young adult patients with cancer and to discuss potential strategies and actions to address them.
Keywords: Health and Medicine

Childhood Cancer Survivorship: Improving Care and Quality of Life - Institute of Medicine; National Research Council (The National Academies Press, 2003)
Only more recently has it been realized that the intense effort to care for and cure a child with cancer does not end with survival. Continued surveillance and a variety of interventions may, in many cases, be needed to identify and care for consequences of treatment that can appear early or only after several decades and impair survivors’ health and quality of life. The more than two-thirds of childhood cancer survivors who experience late effects -- that is, complications, disabilities, or adverse outcomes -- as a result of their disease, its treatment, or both, are the focus of this report which outlines a comprehensive policy agenda that links improved health care delivery and follow-up, investments in education and training for health care providers, and expanded research to improve the long-term outlook for this growing population now exceeding 270,000 Americans.
Keywords: Health and Medicine

Guiding Cancer Control: A Path to Transformation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Throughout history, perhaps no other disease has generated the level of social, scientific, and political discourse or has had the degree of cultural significance as cancer. A collective in the truest sense of the word, "cancer" is a clustering of different diseases that afflict individuals in different ways. Its burdens are equally broad and diverse, from the physical, financial, and psychological tolls it imposes on individuals to the costs it inflicts upon the nation's clinical care and public health systems, and despite decades of concerted efforts often referred to as the "war on cancer", those costs have only continued to grow over time. The causes and effects of cancer are complex—in part preventable and treatable, but also in part unknown, and perhaps even unknowable. Guiding Cancer Control defines the key principles, attributes, methods, and tools needed to achieve the goal of implementing an effective national cancer control plan. This report describes the current structure of cancer control from a local to global scale, identifies necessary goals for the system, and formulates the path towards integrated disease control systems and a cancer-free future. This framework is a crucial step in establishing an effective, efficient, and accountable system for controlling cancer and other diseases.
Keywords: Health and Medicine

Making Better Drugs for Children with Cancer - Institute of Medicine; National Research Council (The National Academies Press, 2005)
The successes that have been achieved in treating childhood cancers stand as beacons against the less dramatic improvements for adults with cancer. Progress began to accelerate in the 1960s and 1970s, as treatment regimens were built up, primarily by building combinations of chemotherapeutic drugs. However the near absence of research in pediatric cancer drug discovery threatens to halt the progress in childhood cancer treatment achieved during the past four decades. Making Better Drugs for Children with Cancer identifies the major issues to be addressed in developing new agents for childhood cancers, the gaps in research and development, and the steps that have been suggested to move the process forward. This report also makes a new proposal to capitalize on today's science to bring new treatments to children's cancers.
Keywords: Health and Medicine

Long-Term Survivorship Care After Cancer Treatment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The 2006 Institute of Medicine (IOM) consensus study report From Cancer Patient to Cancer Survivor: Lost in Transition made recommendations to improve the quality of care that cancer survivors receive, in recognition that cancer survivors are at risk for significant physical, psychosocial, and financial repercussions from cancer and its treatment. Since then, efforts to recognize and address the unique needs of cancer survivors have increased, including an emphasis on improving the evidence base for cancer survivorship care and identifying best practices in the delivery of high-quality cancer survivorship care. To examine progress in cancer survivorship care since the Lost in Transition report, the National Cancer Policy Forum of the National Academies of Sciences, Engineering, and Medicine held a workshop in July 2017, in Washington, DC. Workshop participants highlighted potential opportunities to improve the planning, management, and delivery of cancer survivorship care. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Comprehensive Cancer Care for Children and Their Families: Summary of a Joint Workshop by the Institute of Medicine and the American Cancer Society - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Childhood cancer is an area of oncology that has seen both remarkable progress as well as substantial continuing challenges. While survival rates for some pediatric cancers present a story of success, for many types of pediatric cancers, little progress has been made. Many cancer treatments are known to cause not only significant acute side effects, but also lead to numerous long-term health risks and reduced quality of life. Even in cases where the cancer is considered curable, the consequences of treatment present substantial long-term health and psychosocial concerns for children, their families, their communities, and our health system. To examine specific opportunities and suggestions for driving optimal care delivery supporting survival with high quality of life, the National Cancer Policy Forum of the Institute of Medicine and the American Cancer Society co-hosted a workshop which convened experts and members of the public on March 9 and 10, 2015. At this workshop, clinicians and researchers in pediatric oncology, palliative, and psychosocial care, along with representatives from the U.S. Food and Drug Administration, National Cancer Institute, Children's Oncology Group, pharmaceutical companies, and patient advocacy organizations, discussed and developed a menu of options for action to improve research, quality of care, and outcomes for pediatric cancer patients and their families. In addition, parents of children with cancer and pediatric cancer survivors shared their experiences with care and provided poignant personal perspectives on specific quality of life concerns and support needs for children and families across the life spectrum. This report summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine